2010
DOI: 10.1086/651585
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Carbon Incorporation Rates in Lizards: Implications for Ecological Studies Using Stable Isotopes in Terrestrial Ectotherms

Abstract: Carbon stable isotope (delta(13)C) analysis can be used to infer the origin and to estimate the flow of nutrient resources through animals and across ecological compartments. These applications require knowledge of the rates at which carbon is incorporated into animal tissues and diet-to-tissue discrimination factors (Delta(13)C). Studies of carbon dynamics in terrestrial vertebrates to date have focused almost solely on endothermic animals; ectotherms such as reptiles have received little attention. Here we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
68
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 49 publications
(81 reference statements)
9
68
3
3
Order By: Relevance
“…These observations suggest that: (1) developmental stage and growth rate should be considered before applying captive experimental results to wild subjects, and (2) there is likely individual variation in incorporation rates that are independent of growth. However, it is important to note that the contribution of growth to tissue incorporation rates was lower in this study than has been previously reported for aquatic (Hesslein et al, 1993;MacAvoy et al, 2001;Trueman et al, 2005;MacNeil et al, 2006) and terrestrial (Reich et al, 2008;Warne et al, 2010) ectotherms. Because growth contributed a relatively small portion to tissue incorporation rates, it is unlikely that elasmobranch isotopic incorporation rates are homogenized by growth (e.g.…”
Section: The Contribution Of Growth To Isotopic Incorporation In Leopcontrasting
confidence: 74%
See 2 more Smart Citations
“…These observations suggest that: (1) developmental stage and growth rate should be considered before applying captive experimental results to wild subjects, and (2) there is likely individual variation in incorporation rates that are independent of growth. However, it is important to note that the contribution of growth to tissue incorporation rates was lower in this study than has been previously reported for aquatic (Hesslein et al, 1993;MacAvoy et al, 2001;Trueman et al, 2005;MacNeil et al, 2006) and terrestrial (Reich et al, 2008;Warne et al, 2010) ectotherms. Because growth contributed a relatively small portion to tissue incorporation rates, it is unlikely that elasmobranch isotopic incorporation rates are homogenized by growth (e.g.…”
Section: The Contribution Of Growth To Isotopic Incorporation In Leopcontrasting
confidence: 74%
“…Previous studies on turtles (Reich et al, 2008) and lizards (Warne et al, 2010) found slower incorporation rates in older individuals. The leopard sharks in this study had variable massspecific growth rates (Fig.2), and although smaller individuals generally had faster growth rates, similar-sized individuals sometimes had different growth rates (i.e.…”
Section: The Contribution Of Growth To Isotopic Incorporation In Leopmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, a literature search using Web of Science and combinations of the search terms "isotope," "turnover," "discrimination," and "fractionation" returns C or N isotope discrimination values or turnover rates for at least one tissue from 62 fishes, 41 invertebrates, 30 birds, and 25 mammals. In contrast, isotope parameters are available for only one species of amphibian (McIntyre and Flecker 2006) and eight species of reptile (Seminoff et al 2006(Seminoff et al , 2007(Seminoff et al , 2009Reich et al 2008;Fisk et al 2009;Warne et al 2010;Murray and Wolf 2012). This lack of stable isotope parameters for ectothermic tetrapods limits our overall understanding of stable isotope dynamics, in particular possible differences between large ectothermic and endothermic top predators.…”
mentioning
confidence: 99%
“…Across vertebrate taxa, these TDFs typically range from -0.4 to 7.9‰ for carbon and -0.1 to 4.0‰ for nitrogen (Caut et al 2009), and they often differ among tissues, a phenomenon known as tissue-specific discrimination (Martínez del Rio et al 2009a (Tieszen et al 1983;Hobson and Clark 1992b;Martínez del Rio et al 2009b Lesage et al 2002;MacAvoy et al 2006;Stegall et al 2008;Florin et al 2011;Browning et al 2014). Recent studies have also investigated TDFs and incorporation rates in reptiles (Seminoff et al 2007;Reich et al 2008;Fisk et al 2009;Seminoff et al 2009;Warne et al 2010;Murrary and Wolf 2013).…”
Section: Introductionmentioning
confidence: 99%